Psychology of advertising a new century - Rutsohn, Phil (Florida : D.E. visuals, 2002)
Discusses the psychology behind the buying motive and incorporates that understanding into advertisments. Includes psycho-sociological issues with examples drawn from television ads, print ads, and computer ads on the Internet. Also discusses the interrelationship between the physical components and the message communicated by an advertisement.
DVD format
Keywords: Advertising; Advertising -- Psychological aspects